Application of Oxytocin Massage in Continuity of Care - Sinta Utami Dewi; Amri Wulandari; Nur Fauziandari, Erma (Universitas STRADA Indonesia, 2025)
Exclusive breastfeeding plays an important role in the growth and development of the baby. Milk production can be increased through oxytocin massage. Oxytocin massage is a massage along the spine, which functions to increase oxytocin. The study aimed to determine the results of the application of oxytocin massage on the smooth production of breast milk. This type of research is qualitative with a case study research method using the Continuity Of Care midwifery care approach which is carried out continuously from pregnancy to the postpartum period. This oxytocin massage is done during the first 5 days postpartum, where in 1 day 1 massage is done in the afternoon for 10-15 minutes. Oxytocin massage evaluation was carried out on the 6th day. The result of the study showed that after the oxytocin massage, the mother felt calmer and more relaxed, and the milk production increased as evidenced by the increase in the baby's weight for 6 days. Oxytocin massage has been proven to facilitate breast milkproduction as seen from the baby's weight gain of 300 grams.